Detailed Measurement of Wall Strain with 3D Speckle Tracking in the Aortic Root: A Case of Bionic Support for Clinical Decision Making - Vogt, Sebastian; Karatolios, Konstantinos; Wittek, Andreas; Blasé, Christopher; Ramaswamy, Anette; Mirow, Nikolas; Moosdorf, Rainer (The Thoracic and Cardiovascular Surgeon Reports, 2016)
Three-dimensional (3D) wall motion tracking (WMT) based on ultrasound imaging enables estimation of aortic wall motion and deformation. It provides insights into changes in vascular compliance and vessel wall properties essential for understanding the pathogenesis and progression of aortic diseases. In this report, we employed the novel 3D WMT analysis on the ascending aorta aneurysm (AA) to estimate local aortic wall motion and strain in case of a patient scheduled for replacement of the aortic root. Although progression of the diameter indicates surgical therapy, at present we addressed the question for optimal surgical time point. According to the data, AA in our case has enlarged diameter and subsequent reduced circumferential wall strain, but area tracking data reveals almost normal elastic properties. Virtual remodeling of the aortic root opens a play list for different loading conditions to determine optimal surgical intervention in time.
Keywords: aortic disease; aneurysm; biomechanics; echocardiography